Technology-supported Project-based Learning: Trends, Review and Future Research in Science, Technology and Engineering Education - Wahyudi, W.; Setiawan, Agus; Suhandi, Andi; Samsudin, Achmad (ASEAN Journal of Science and Engineering, 2024)
This research investigates trends in technology-supported project-based learning (PjBL) in science, technology, and engineering education and also provides future research directions in this field. Bibliometric analysis with Scopus database sources in the period 2004-2023 was used in this investigation. 541 publications met the criteria, with the annual growth of publications increasing based on the number of documents and citations. American and Asian countries are the most productive countries and affiliates in publications in this field. Most publications are produced from international conferences. The publication's conceptual structure shows four research clusters with 81 terms, 1029 links, and a total link strength of 3492. The term "project-based learning" is the central node in the cluster, connecting several essential terms related to the use of technology in PjBL. The discussion at the end of this study leads to recommended further research paths for developing technology-supported PjBL.